WATER RESOURCES AS THE SAFETY FACTOR IN CENTRAL ASIA (International relations and international law Journal, 2016)
The author considers the situation with water resources in Central Asia as a hypothetical area for domestic or interstate conflicts. Effective management of water resources is a crucial factor for development of this region.
Keywords: water resources; safety; Central Asia